IrO2-Ta2O5 Anode for Oxygen Evolution with TaOx Interlayer Prepared by Thermal Decomposition in Inert Atmosphere. Issue 4 (1st April 2022) - Liu, Yueren; Xu, Likun; Xin, Yonglei; Liu, Feng; Xuan, Junji; Guo, Mingshuai; Duan, Tigang
Abstract : A novel IrO2 -Ta2 O5 coated titanium anode with TaOx interlayer was prepared using a facile method of thermal decomposition. The interlayer and the composite anodes of Ti/TaOx /IrO2 -Ta2 O5 were characterized with surface analytical techniques of XPS, XRD, SEM and EDS. The electrochemical properties of the composite anodes with different coats of the interlayer were measured using anodic polarization, CV, EIS and accelerated life testing. The results showed that the TaOx interlayer was amorphous consisting of multivalent Ta oxides. The electrocatalytic activity for oxygen evolution reaction and the stability of the composite anodes were improved obviously with adding the TaOx interlayer of appropriate thickness, which can be attributed to the increase of electrochemically active sites and the extra protection for Ti substrate by the non-stoichiometric TaOx interlayer.